The phenomenon of anticipation in fencing. An applicability approach - Borysiuk, Z.; Konieczny, M.; Blaszczyszyn, M.; Blach, W.; Obminski, Z. (Frontiers in Sports and Active Living, 2024)
Introduction: The aim of the study was to determine the structure of muscular activity and ground reaction forces during the preparatory period and the execution of a fencing lunge at the opponent's torso. The analysis focused on the correlations between three phases of a fencing technical action in the context of factors of temporal anticipation.